1988
DOI: 10.1159/000167602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Calcium Channel Blocker Nisoldipine on the Progression of Chronic Renal Failure in Man

Abstract: Patients with stable renal insufficiency were randomized into two groups: (1) patients given the channel blocker nisoldipine (n = 17) and (2) placebo-treated patients (n = 17) also taking their regular antihypertensive therapy which did not include calcium blockers. Patients were already on low protein diet with a protein intake of 0.80 ± 0.2 in the nisoldipine group versus 0.85 ± 0.25 g/kg body weight in the placebo-treated group. The monthly progression of their renal failure was assessed by the reciprocal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…This is in contrast to their find ings that similar control of hypertension produced by chlorothalidonc and furosemide, ß-blockers, prazosin or hydralazine did not prevent the progession of renal fail ure. Thus, the study of Eliahou et al [24] also demon strated, as our study does, that the control of hypertension per sc may not be adequate to prevent the deterioration in renal function. Furthermore, others have reported that converting enzyme inhibitors are more potent in prevent ing the progression of renal insufficiency than other anti hypertensive agents [25,26], and the long-term therapy of patients with renal failure and hypertension with enalapril may increase the glomerular filtration rate [27], Anderson and Brenner [28] suggested that the different effects of antihypertensive drugs on renal function, de spite comparable control of hypertension, are due to dif ferent actions on systemic and glomerular hypertension.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…This is in contrast to their find ings that similar control of hypertension produced by chlorothalidonc and furosemide, ß-blockers, prazosin or hydralazine did not prevent the progession of renal fail ure. Thus, the study of Eliahou et al [24] also demon strated, as our study does, that the control of hypertension per sc may not be adequate to prevent the deterioration in renal function. Furthermore, others have reported that converting enzyme inhibitors are more potent in prevent ing the progression of renal insufficiency than other anti hypertensive agents [25,26], and the long-term therapy of patients with renal failure and hypertension with enalapril may increase the glomerular filtration rate [27], Anderson and Brenner [28] suggested that the different effects of antihypertensive drugs on renal function, de spite comparable control of hypertension, are due to dif ferent actions on systemic and glomerular hypertension.…”
Section: Discussionsupporting
confidence: 39%
“…Calcium channel blockers may also induce renal vaso dilatation, natriuresis and an increase in glomerular filtra tion in patients with essential hypertension [23], Eliahou et al [24] reported that the calcium channel blocker, nisoldipine, reduced blood pressure and ameliorated the pro gression of renal failure. This is in contrast to their find ings that similar control of hypertension produced by chlorothalidonc and furosemide, ß-blockers, prazosin or hydralazine did not prevent the progession of renal fail ure.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have been shown to reduce systemic blood pressure -O lomerular filtration rate: UAE = urinary protein while maintaining GFR and renal plasma flow in short term studies [39], and to protect residual renal function [40], especially when given to patients with only moderately impaired GFR [41], in long-term studies.…”
Section: Acei Versus Caa In Imondiabetic Renal Diseasementioning
confidence: 99%
“…In humans, the effect of calcium antagonists on proteinuria is variable as it seems to depend on the agent used and the patients treated. Nisoldipine has no effect on proteinuria in pa tients with progressive CRF, in spite of a significant reduction in their diastolic blood pressure and an im provement in the rate of decline of renal function [8]. In insulin-dependent diabetic patients, nifedipine seems to increase albuminuria [18], whilst nicardipine has no effect on that of patients with type 11 diabetes [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, whilst ACE inhi bitors have consistently proved effective at preventing progressive experimental renal insufficiency and scar ring [4], the data with calcium antagonists are somewhat conflicting [5,6]. In patients with CRF, it has also been claimed that ACE inhibitors [7] and calcium antagonists [8] are more effective at slowing the progression of renal insufficiency than conventional antihypertensive agents. Whether the presumed beneficial effect of calcium anta gonists on progressive CRF in humans is due solely to their effect on systemic hypertension remains to be deter mined.…”
Section: Introductionmentioning
confidence: 99%